Wellbeing 2014
DOI: 10.1002/9781118539415.wbwell036
|View full text |Cite
|
Sign up to set email alerts
|

The State of Wellbeing Science

Abstract: In this introductory chapter, some of the fundamental questions concerning the nature and importance of subjective wellbeing are addressed, and how wellbeing concepts and measures can be effectively integrated into interventions and policy. The chapter begins by asking what wellbeing is, and differentiating the concepts of positive mental health or flourishing from the absence of illbeing. It then tackles the issue of whether positive mental health and mental disorders should be regarded as lying along a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 153 publications
2
51
0
Order By: Relevance
“…On the other hand, emotional demands, such as, hide emotions and simulate good mood and/or empathy, are also linked to well-being. These results are in accordance with other studies on the impact of work relations and emotional demands, and underlines the role and contribution of social support, social relationships in occupational health and wellbeing [43][44][45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, emotional demands, such as, hide emotions and simulate good mood and/or empathy, are also linked to well-being. These results are in accordance with other studies on the impact of work relations and emotional demands, and underlines the role and contribution of social support, social relationships in occupational health and wellbeing [43][44][45].…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that Portuguese healthcare workers can positively cope with the strains of professional life, and work productively and usefully [9]. Feeling good all the time will not be conductive to well-being, since negative and painful emotions play an important part in daily life when experienced in the appropriate context, such as feeling anger following injustice [42]. Regarding the work-related risk factors, this study showed that most of the participants are exposed to several risk factors at workplace (ranging from environmental risk factors, biological to physical), although the psychosocial risk factors (work relations with superiors and colleagues, employment relations, and emotional demands) are the ones that most impact on well-being.…”
Section: Discussionmentioning
confidence: 94%
“…5 This is especially true among those with childhood-onset chronic health conditions, such as type 1 diabetes. 6 Adult psychological well-being has many dimensions, [7][8][9] and its subjective evaluation is based on 2 primary frameworks. [10][11][12] The hedonic framework considers the experience of emotion, both positive and negative, with a focus on happiness and the evaluation of life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous findings, it is clear that with proper design, the smart spaces can be used for supporting user's wellbeing. Wellbeing can be seen from different perspectives: as a general phenomenon, or as an objective or subjective wellbeing of a person [9]. Subjective wellbeing of a person is connected into person's emotions which are usually triggered by an implicit cause (e.g., some event) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Subjective wellbeing of a person is connected into person's emotions which are usually triggered by an implicit cause (e.g., some event) [6]. One of the key impacting factors for peoples' subjective wellbeing is the living environment and as people spend half of their lives in work, it is crucial to support wellbeing at work too [9]. The WELL building standard [4] focuses on health and wellbeing of people occupying the buildings and it is aimed for all stakeholders involved in the construction and use of the buildings.…”
Section: Introductionmentioning
confidence: 99%